Agricultural students’ attitude towards agricultural entrepreneur as a career - Mat Sulaiman, Nur Nadzirah (2017)
Despite of food security tribulation and slow economic growth, agriculture entrepreneur is a high potential and important career that requires deep passion and enthusiast attitude. However, many agricultural graduates did not become an entrepreneur due to many internal and external factors that become their perception reflected in their attitude. Therefore, the general objective of this study determines the perception level of respondents’ attitude towards agriculture field and agriculture entrepreneur as their future career. Specifically this study aims to identify the factors that influencing students in becoming agriculture entrepreneur. A quantitative approach using case study survey by giving out questionnaires was used to gather data from 200 youths taking agricultural courses located in the nation's research university, Universiti Putra Malaysia Later, the collected response are analysed by using descriptive and factor analysis in SPSS software. In this study, 92.5% of respondents think that agricultural job promises hefty profit if pursued with correct way while 83% responses indicate interest and passion as requirement to involve in agriculture are the most important drive to do work successfully in this field. In contrast,86% perceived that limited capital is the main problems and constraints for their involvement in agriculture sector which consequently lead to 95% result that they will definitely agree to choose and involved in agriculture sector if no barrier factor as earlier Similarly, based on factor analysis, the five factors of government policy and support, social and society, individual, family support and institution that influence participation and interest of youth towards agriculture entrepreneur With respect to the increasing youth awareness on the importance of this sector, it is then essential that agriculture promoting strategies to increase the knowledge and technology transfer are made in more efficient way. In conjunctions with that, agriculture awareness campaign through mass media; allowing access for information about commercial agriculture such as agricultural technology and the government incentive should be more viral. Moreover, facilities for agriculture product marketing and technical service application of agricultural technology should be improved. Therefore, government policy makers and other authorities need to understand youth behaviour towards agriculture entrepreneur as career can be improved by their access of information to government incentive, institution role and also social factor such as family and community support.